Assessment of vegetative, neurohumoral and psycho-emotional disorders in patients with atopic dermatitis of varying severity - A. V. Patrushev; V. O. Gutka; A. V. Sukharev; A. V. Samtsov; E. I. Zavalskaya (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal of the study. evaluation of psycho-vegetative disorders in patients with atopic dermatitis, and the determination of their influence on the severity of the disease. Material and methods. The study involved 72 patients with atopic dermatitis aged 18 to 46 years (men - 41, women - 31). The control group, similar in age and sex characteristics, and 30 healthy volunteers. All patients underwent an individual computer study psychophysiological and emotional state of a human body with a digital telemetry hardware and software system - analyzer of biorhythms «Omega-M» Scientific-production company «Dynamics» (Saint-Petersburg). Evaluates the performance of the autonomic, neurohumoral and central regulation, as well as the integral indicators of the functional state of the organism. Quality of life assessed by questionnaire DLQI (dermatology life quality index), the severity of the disease was determined by the index SCORAD (scoring atopic dermatitis). Results. Autonomic disorders were diagnosed in 75.0% of patients (54/72), represented mainly sympathicotonia and centralization of heart rhythm. Neurodynamic methods and fractal analysis of cardiac rhythm disorders of neurohumoral regulation and psycho-emotional diagnosed respectively in 69.4% (50/72) and 76.6% (53/72) of patients with atopic dermatitis. A moderate correlation between the severity of the disease and some indicators (IV, IVE, VR, C1, D1) showing violations of the vegetative and central regulation (0,25 < IrsI < 0,75).